2014
DOI: 10.1111/jvp.12127
|View full text |Cite
|
Sign up to set email alerts
|

Plasma disposition kinetics of moxidectin after subcutaneous administration to pregnant sheep

Abstract: The plasma kinetic profile of moxidectin (MXD) in ewes during the last third of pregnancy was studied after the subcutaneous dose of 0.2 mg/kg of body weight (bw). Two groups of sheep (n = 7) that were equally balanced in body weight were used. Group I (control) was maintained unmated, while Group II (pregnant) was estrous-synchronized and mated with fertile rams. Both groups were maintained under similar conditions regarding management and feeding. When the ewes from Group II fulfilled 120 days of pregnancy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In in vivo studies, the C max /dose and AUC 0 – t /dose of the MXD-TG preparation were 323.49 ± 128.57 ng mL −1 mg −1 kg and 3285.56 ± 1582.40 days ng mL −1 mg −1 kg, respectively. The C max /dose and AUC 0 – t /dose of the commercial MXD formulation was 42 ± 28.5 ng mL −1 mg −1 kg and 1094 ± 188.5 days ng mL −1 mg −1 kg [ 32 ], respectively. It was shown that MXD could be absorbed quickly and distributed widely after subcutaneous administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In in vivo studies, the C max /dose and AUC 0 – t /dose of the MXD-TG preparation were 323.49 ± 128.57 ng mL −1 mg −1 kg and 3285.56 ± 1582.40 days ng mL −1 mg −1 kg, respectively. The C max /dose and AUC 0 – t /dose of the commercial MXD formulation was 42 ± 28.5 ng mL −1 mg −1 kg and 1094 ± 188.5 days ng mL −1 mg −1 kg [ 32 ], respectively. It was shown that MXD could be absorbed quickly and distributed widely after subcutaneous administration.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing with the oral formulation, the concentration of MXD was too low to be detected in the plasma after 42 days of administration at 0.2 mg/kg [ 33 ]. Meanwhile, the MXD concentration remained above 1 ng/mL when treated with a subcutaneous administration at 0.2 mg/kg during the 40 days of the experiment period [ 32 ]. The maintenance time of MXD was shorter than that of the MXD-TG preparation in the plasma of sheep.…”
Section: Discussionmentioning
confidence: 99%
“…In cattle, when MXD was administered s.c. (0.2 mg/kg BW), orally (0.2 mg/kg BW), and topically (0.5 mg/kg BW), the AUCs were 105.64, 20.88, and 9.14 ng hr ml −1 , respectively (Leathwick & Miller, ). The AUCs of MXD at 0.2 mg/kg after s.c. administration to nonpregnant and pregnant sheep were 109.8 ± 37.3 ng hr ml −1 and 143.6 ± 24.7 ng hr ml −1 , respectively (Perez et al., ). The AUC value following s.c. and oral administrations at the same dose of 0.2 mg/kg in sheep was 112 ng hr ml −1 and 99 ng hr ml −1 , respectively (McKellar & Benchaoui, ); and 3280.8 ng hr ml −1 and 880.8 ng hr ml −1 , respectively, in goats (Escudero et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…To make better use of the antiparasitic effect of MXD, it is imperative to characterize the plasma disposition kinetics of the drug. The pharmacokinetics of MXD have been widely reported in many species such as rabbits which were given MXD topically at a dose of 1 mg/kg BW (Pan et al., ), goats which were given subcutaneously (s.c.) and orally at 0.2 mg/kg BW (Escudero et al., ), sheep which were given s.c. at 0.2 mg/kg BW (Perez, Nunez, Palma, Riquelme, & Arboix, ), and cattle which were given orally, s.c., and topically at 0.2, 0.2, and 0.5 mg/kg BW, respectively (Leathwick & Miller, ). In pigs with different body fat content, the plasma kinetic profile of MXD was studied, and results showed that comparing to fat pigs, lean pigs had more rapid distribution and elimination rate than fat pigs when MXD was administered intravenously (i.v.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation